From bench to bioterium and back again: development of a U1snRNA-based therapeutic strategy for mucopolysaccharidosis IIIC - Santos, Juliana Inês (2021)
Splicing is an essential cellular process to generate mature transcripts from pre-mRNA. One of the most important factors for mRNA transcription is the U1snRNA, a spliceosomal component that recognizes 5’ splicing donor sites (SDS) at specific regions in pre-mRNA. Splicing mutations represent one of the most frequent (~20%) genetic defects in Mucopolysaccharidosis IIIC (MPS IIIC), a Lysosomal Storage Disorder (LSD) caused by mutations in the HGSNAT gene, encoding an enzyme involved in heparan sulphate degradation. . Exon-skipping has been demonstrated as, probably, the most frequent aberrant splicing defect, and occurs due to mutations in the 5’ SDS. Application of modified U1snRNAs to improve recognition of mutated 5’ SDS represent a potential therapeutic strategy to recover the normal splicing process. The c.234+1G>A is a frequent mutation among patients of countries around the Mediterranean basin (Portugal, Spain, Morocco and Tunisia). It’s located in the + 1 position of intron 2 of HGSNAT gene and leads to the skipping of exon 2. We demonstrated in fibroblast cells that a modified U1snRNA vector (comprising exon 1 to exon 3) designed to improve the definition of exon 2 5’ SDS of the HGSNAT can restore the splicing defect caused by the mutation c.234+1G>A (Matos et al., 2014). Currently our goal is to evaluate in vivo the therapeutic potential of the modified U1 snRNA by testing it in mice expressing the human splicing defect.